1974
DOI: 10.1071/ar9740369
|View full text |Cite
|
Sign up to set email alerts
|

A sand culture experiment to compare the effects of sulphur on five wheat cultivars (T. aestivum L.)

Abstract: A glasshouse sand culture experiment was conducted to determine the effects of sulphur supplied at 10,375 and 875µM concentrations on total dry matter production per plant (TDM), grain yield, harvest index (HI), yield components, nitrogen, sulphur and phosphorus levels in herbage and grain samples of two vitreous grained (Stockade and Gabo) and three non-vitreous grained (Insignia, Olympic and Summit) wheat cultivars (T. aestivum L.). Pelshenke doughball fermentation tests were done on wholemeal samples from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
4

Year Published

1979
1979
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 5 publications
1
9
0
4
Order By: Relevance
“…Sulfur application has been reported to decrease (Byers and Bolton 1979) or increase (Archer 1974) grain nitrogen. The present experiments, over a wider range of sulfur supply levels, have shown (Tables 2 and 3) that an increment of applied sulfur may increase or decrease grain nitrogen or have no effect, depending on the sulfur status and the nitrogen supply.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sulfur application has been reported to decrease (Byers and Bolton 1979) or increase (Archer 1974) grain nitrogen. The present experiments, over a wider range of sulfur supply levels, have shown (Tables 2 and 3) that an increment of applied sulfur may increase or decrease grain nitrogen or have no effect, depending on the sulfur status and the nitrogen supply.…”
Section: Discussionmentioning
confidence: 98%
“…The wide (N/S), ratios of sulfur-sufficient samples represented in area B could be due to high nitrogen supply especially during grain filling or to an accumulation of nitrogen due to a limitation on yield by some other factor. Data from Archer (1974) and Byers and Bolton (1979) are also plotted. These represent a range of cultivars and culture conditions but embrace a limited number of sulfur treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This variation in sulphur requirement is due to soil type, climate and cropping system (Zhao et al, 1999a). Several greenhouse and field studies reported that sulphur primarily affects the number of grains per spike indicating that sulphur deficiency increases the mortality of florets or reduces the initiation of florets (Archer, 1974;Islam et al, 1999). Other yield components such as number of tillers and thousand grain weight are less affected by sulphur availability unless the deficiency is severe.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in totai yield and oil content due to Zn and S deficiency in Brassica seeds was found by Singh et al (1975) and could be ascribed to slower translocation of photosynthates to the developing seeds (Archer 1974). A study of sucrose-starch conversion during mineral deficiency would help understand the low starch accumulation during the early stages of seed development.…”
Section: Discussionmentioning
confidence: 87%
“…Zinc also regulates the activity of a number of other enzymes (Vallee 1983) which furnish the precursors for fatty acid synthesis. Suiphur is Phvsiol, Piam, 80, 1990 required for the synthesis of proteins (Ergie 1953) including the acyi carrier proteins (Ohlrogge et al 1979) and mobOizes metabolites (Archer 1974) for the enhanced biosynthesis of lipids in oilseeds (Sukhija et al 1987). It is expected that S deficiency causes a decrease in protein synthesis (Wrigley et ai.…”
Section: Discussionmentioning
confidence: 99%